Impact of Macroeconomic Variables on Stock Market Performance: Evidence from Sri Lanka - Balagobei, S.; Bandara, D.R.N.K.K. (Wayamba University of Sri Lanka, 2022)
The aim of the paper is to explore the influence of macroeconomic variables on stock market performance in Sri Lanka. The proxy for the stock market performance is all share price index (ASPI) whereas Gross domestic product (GDP), inflation rate, interest rate, exchange rate and money supply are considered as macroeconomic variables. The population of the study consists of all companies listed in Colombo Stock Exchange. The data was gathered from the secondary sources and the annual time series data was employed from 1995 to 2019. The techniques of Pearson’s correlation and multiple regressions were employed for the data analysis and hypothesis testing. Furthermore, Variance inflation factor (VIF) for Multicollinearity, Augmented Dicky–Fuller (ADF) test and Breusch-Pagan-Godfrey test were used. The findings demonstrate that GDP and money supply positively influence the stock market performance. Interest rate and exchange rate negatively influence the stock market performance while inflation rate has failed to prove the significant impact on stock market performance. The study will support to investors, academics and researchers in the fields of economics and finance in understanding how macroeconomic variables affect the stock market performance. It also provides insight into society and researchers since it integrates a number of macroeconomic variables and their interaction with the stock market.
Keywords: Gross domestic product; Exchange rate; Interest rate; Money supply; Stock market performance